Sarcostemma viminale activates macrophages to a pro-inflammatory phenotype - Brestovac, Brian; Coghlan, O.; Jackaman, Connie; Nelson, Delia; Townsend, D. (2014)
Sarcostemma viminale (L.) R.Br, also known as caustic or milk bush, is a semi-succulent plant commonly found in the North West of Australia. Local Aboriginal populations have long used the milky white sap from this plant to treat skin cancers. An ethanol extract from S. viminale was tested by exposing the RAW264.7 cell line as an in vitro murine macrophage model, to the extract. Flow cytometric analysis was performed to determine if S. viminale skewed macrophages towards a pro-inflammatory or anti-inflammatory phenotype using a number of cell surface markers. Cell culture supernatants were also analysed by cytometric bead array to determine if S. viminale exposed macrophages produced pro-inflammatory or anti-inflammatory cytokines. After exposure to S. viminale, a significantly greater number of macrophages expressed pro-inflammatory major histocompatibility complex (MHC) class II molecules and significantly greater expression levels of the dendritic cell marker CD11c. Cytometric bead array analysis found that S. viminale induced significant amounts of the potent pro-inflammatory cytokine tumour necrosis factor (TNF) from macrophages. The markers CD40 and ICAM-1 were expressed but were not significantly different from the controls. Also, significantly higher expression of CX3CR1 indicated that macrophages were preparing to migrate. No anti-inflammatory cytokines were produced. No significant production of NO2-, IL-6, IFN-? or IL-12 was found. These results demonstrate that S. viminale drives resting macrophages into a pro-inflammatory phenotype, reminiscent of activated immature dendritic cells. If this activation could be achieved in the peri-tumour environment, then S. viminale could be useful as an adjunct therapy for skin cancer. © 2014 Springer-Verlag London.